{-# LANGUAGE CPP #-} {-# LANGUAGE TypeOperators #-} #ifdef __GLASGOW_HASKELL__ #define LANGUAGE_DeriveDataTypeable {-# LANGUAGE DeriveDataTypeable #-} #endif #ifndef MIN_VERSION_tagged #define MIN_VERSION_tagged(x,y,z) 1 #endif #ifndef MIN_VERSION_base #define MIN_VERSION_base(x,y,z) 1 #endif #if defined(__GLASGOW_HASKELL__) && __GLASGOW_HASKELL__ >= 702 #if MIN_VERSION_transformers(0,3,0) && MIN_VERSION_tagged(0,6,1) {-# LANGUAGE Safe #-} #else {-# LANGUAGE Trustworthy #-} #endif #endif ----------------------------------------------------------------------------- -- | -- Module : Data.Functor.Contravariant -- Copyright : (C) 2007-2014 Edward Kmett -- License : BSD-style (see the file LICENSE) -- -- Maintainer : Edward Kmett -- Stability : provisional -- Portability : portable -- -- 'Contravariant' functors, sometimes referred to colloquially as @Cofunctor@, -- even though the dual of a 'Functor' is just a 'Functor'. As with 'Functor' -- the definition of 'Contravariant' for a given ADT is unambiguous. ---------------------------------------------------------------------------- module Data.Functor.Contravariant ( -- * Contravariant Functors Contravariant(..) -- * Operators , (>$<), (>$$<) -- * Predicates , Predicate(..) -- * Comparisons , Comparison(..) , defaultComparison -- * Equivalence Relations , Equivalence(..) , defaultEquivalence , comparisonEquivalence -- * Dual arrows , Op(..) ) where import Control.Applicative import Control.Applicative.Backwards import Control.Category import Data.Functor.Product import Data.Functor.Sum import Data.Functor.Constant import Data.Functor.Compose import Data.Functor.Reverse import Data.Semigroup (Semigroup(..), Monoid(..)) #ifdef LANGUAGE_DeriveDataTypeable import Data.Typeable #endif #if defined(__GLASGOW_HASKELL__) && __GLASGOW_HASKELL__ < 707 && defined(VERSION_tagged) import Data.Proxy #endif #if defined(__GLASGOW_HASKELL__) && __GLASGOW_HASKELL__ >= 702 #define GHC_GENERICS import GHC.Generics #endif import Prelude hiding ((.),id) -- | Any instance should be subject to the following laws: -- -- > contramap id = id -- > contramap f . contramap g = contramap (g . f) -- -- Note, that the second law follows from the free theorem of the type of -- 'contramap' and the first law, so you need only check that the former -- condition holds. class Contravariant f where contramap :: (a -> b) -> f b -> f a -- | Replace all locations in the output with the same value. -- The default definition is @'contramap' . 'const'@, but this may be -- overridden with a more efficient version. (>$) :: b -> f b -> f a (>$) = contramap . const infixl 4 >$, >$<, >$$< (>$<) :: Contravariant f => (a -> b) -> f b -> f a (>$<) = contramap {-# INLINE (>$<) #-} (>$$<) :: Contravariant f => f b -> (a -> b) -> f a (>$$<) = flip contramap {-# INLINE (>$$<) #-} #ifdef GHC_GENERICS instance Contravariant V1 where contramap _ x = x `seq` undefined instance Contravariant U1 where contramap _ U1 = U1 instance Contravariant f => Contravariant (Rec1 f) where contramap f (Rec1 fp)= Rec1 (contramap f fp) instance Contravariant f => Contravariant (M1 i c f) where contramap f (M1 fp) = M1 (contramap f fp) instance Contravariant (K1 i c) where contramap _ (K1 c) = K1 c instance (Contravariant f, Contravariant g) => Contravariant (f :*: g) where contramap f (xs :*: ys) = contramap f xs :*: contramap f ys instance (Functor f, Contravariant g) => Contravariant (f :.: g) where contramap f (Comp1 fg) = Comp1 (fmap (contramap f) fg) {-# INLINE contramap #-} instance (Contravariant f, Contravariant g) => Contravariant (f :+: g) where contramap f (L1 xs) = L1 (contramap f xs) contramap f (R1 ys) = R1 (contramap f ys) #endif instance (Contravariant f, Contravariant g) => Contravariant (Sum f g) where contramap f (InL xs) = InL (contramap f xs) contramap f (InR ys) = InR (contramap f ys) instance (Contravariant f, Contravariant g) => Contravariant (Product f g) where contramap f (Pair a b) = Pair (contramap f a) (contramap f b) instance Contravariant (Constant a) where contramap _ (Constant a) = Constant a instance Contravariant (Const a) where contramap _ (Const a) = Const a instance (Functor f, Contravariant g) => Contravariant (Compose f g) where contramap f (Compose fga) = Compose (fmap (contramap f) fga) {-# INLINE contramap #-} instance Contravariant f => Contravariant (Backwards f) where contramap f = Backwards . contramap f . forwards {-# INLINE contramap #-} instance Contravariant f => Contravariant (Reverse f) where contramap f = Reverse . contramap f . getReverse {-# INLINE contramap #-} #if (defined(__GLASGOW_HASKELL__) && __GLASGOW_HASKELL__ >= 707) || defined(VERSION_tagged) instance Contravariant Proxy where contramap _ Proxy = Proxy #endif newtype Predicate a = Predicate { getPredicate :: a -> Bool } #ifdef LANGUAGE_DeriveDataTypeable deriving Typeable #endif -- | A 'Predicate' is a 'Contravariant' 'Functor', because 'contramap' can -- apply its function argument to the input of the predicate. instance Contravariant Predicate where contramap f g = Predicate $ getPredicate g . f -- | Defines a total ordering on a type as per 'compare' newtype Comparison a = Comparison { getComparison :: a -> a -> Ordering } #ifdef LANGUAGE_DeriveDataTypeable deriving Typeable #endif -- | A 'Comparison' is a 'Contravariant' 'Functor', because 'contramap' can -- apply its function argument to each input to each input to the -- comparison function. instance Contravariant Comparison where contramap f g = Comparison $ \a b -> getComparison g (f a) (f b) instance Semigroup (Comparison a) where Comparison p <> Comparison q = Comparison $ mappend p q instance Monoid (Comparison a) where mempty = Comparison (\_ _ -> EQ) mappend (Comparison p) (Comparison q) = Comparison $ mappend p q -- | Compare using 'compare' defaultComparison :: Ord a => Comparison a defaultComparison = Comparison compare -- | Define an equivalence relation newtype Equivalence a = Equivalence { getEquivalence :: a -> a -> Bool } #ifdef LANGUAGE_DeriveDataTypeable deriving Typeable #endif -- | Equivalence relations are 'Contravariant', because you can -- apply the contramapped function to each input to the equivalence -- relation. instance Contravariant Equivalence where contramap f g = Equivalence $ \a b -> getEquivalence g (f a) (f b) instance Semigroup (Equivalence a) where Equivalence p <> Equivalence q = Equivalence $ \a b -> p a b && q a b instance Monoid (Equivalence a) where mempty = Equivalence (\_ _ -> True) mappend (Equivalence p) (Equivalence q) = Equivalence $ \a b -> p a b && q a b -- | Check for equivalence with '==' defaultEquivalence :: Eq a => Equivalence a defaultEquivalence = Equivalence (==) comparisonEquivalence :: Comparison a -> Equivalence a comparisonEquivalence (Comparison p) = Equivalence $ \a b -> p a b == EQ -- | Dual function arrows. newtype Op a b = Op { getOp :: b -> a } #ifdef LANGUAGE_DeriveDataTypeable deriving Typeable #endif instance Category Op where id = Op id Op f . Op g = Op (g . f) instance Contravariant (Op a) where contramap f g = Op (getOp g . f) instance Semigroup a => Semigroup (Op a b) where Op p <> Op q = Op $ \a -> p a <> q a instance Monoid a => Monoid (Op a b) where mempty = Op (const mempty) mappend (Op p) (Op q) = Op $ \a -> mappend (p a) (q a) #if MIN_VERSION_base(4,5,0) instance Num a => Num (Op a b) where Op f + Op g = Op $ \a -> f a + g a Op f * Op g = Op $ \a -> f a * g a Op f - Op g = Op $ \a -> f a - g a abs (Op f) = Op $ abs . f signum (Op f) = Op $ signum . f fromInteger = Op . const . fromInteger instance Fractional a => Fractional (Op a b) where Op f / Op g = Op $ \a -> f a / g a recip (Op f) = Op $ recip . f fromRational = Op . const . fromRational instance Floating a => Floating (Op a b) where pi = Op $ const pi exp (Op f) = Op $ exp . f sqrt (Op f) = Op $ sqrt . f log (Op f) = Op $ log . f sin (Op f) = Op $ sin . f tan (Op f) = Op $ tan . f cos (Op f) = Op $ cos . f asin (Op f) = Op $ asin . f atan (Op f) = Op $ atan . f acos (Op f) = Op $ acos . f sinh (Op f) = Op $ sinh . f tanh (Op f) = Op $ tanh . f cosh (Op f) = Op $ cosh . f asinh (Op f) = Op $ asinh . f atanh (Op f) = Op $ atanh . f acosh (Op f) = Op $ acosh . f Op f ** Op g = Op $ \a -> f a ** g a logBase (Op f) (Op g) = Op $ \a -> logBase (f a) (g a) #endif